Physical strength and dance attractiveness: Further evidence for an association in men, but not in women. Issue 5 (7th March 2015) - Weege, Bettina; Pham, Michael N.; Shackelford, Todd K.; Fink, Bernhard
<x xml:space="preserve">Abstract</x> Objectives Physical strength provides information about male quality and can be assessed from facial and body morphology. Research on perception of dance movements indicates that body movement also provides information about male physical strength. These relationships have not been investigated for women. Methods We investigated relationships of handgrip strength (HGS) and dance attractiveness perception in 75 men and 84 women. Results We identified positive relationships between HGS and opposite‐sex assessments of dance attractiveness for men but not women. Conclusions The replication of previous research investigating relationships between dance attractiveness and physical strength in men corroborates the hypothesis that dance movements provide information about male quality. We argue that these relationships are interpretable in contexts of inter‐ and intra‐sexual selection. Am. J. Hum. Biol. 27:728–730, 2015. © 2015 Wiley Periodicals, Inc.